Binding Studies of Pectin in Presence of Divalent Cations - Surabhi, Ajit K.; Williams, Peter A.; Elzagheid, Mohamed. I. (Asian Journal of Chemistry, 2017)
The absorption capacity of low methoxy hydrated and amidated pectins to various metal cations and their effects on rheological properties due to binding of metal cations were investigated. Individual and competitive binding experiments were carried out using low-methoxy hydrated and amidated pectin solutions contained in dialysis bags and using metal cation solutions as the dialyzate. Equilibration took up to 40 h. The metal ions bound were in the order Mn2+ > Fe2+ > Cu2+ > Ca2+ > Zn2+. Calcium binding experiments were undertaken at various pH levels in order to find out the optimum pH values for maximum binding, that for calcium being pH 5.